Front Cover: Identification of Novel Histone Deacetylase 6‐Selective Inhibitors Bearing 3, 3, 3‐Trifluorolactic Amide (TFLAM) Motif as a Zinc Binding Group (ChemBioChem 22/2021). (22nd July 2021) - Kurohara, Takashi; Tanaka, Keita; Takahashi, Daisuke; Ueda, Satoshi; Yamashita, Yasunobu; Takada, Yuri; Takeshima, Hirokazu; Yu, Shengwang; Itoh, Yukihiro; Hase, Koji; Suzuki, Takayoshi
Abstract : This picture shows the 3, 3, 3‐trifluorolactic amide (TFLAM) motif which chelates the zinc ion of histone deacetylase 6 (HDAC6). To identify non‐hydroxamate HDAC6 inhibitors for the treatment of cancer and immunological diseases, the TFMAL motif was discovered by screening a metal chelator chemical library. Subsequent structure‐based drug design led to the discovery of compounds that exhibit sufficient HDAC6 inhibitory activity and selectivity in both in vitro and in cellulo experiments. More information can be found in the Communication by T. Suzuki et al.